2017
DOI: 10.19082/5940
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between cartilage oligomeric matrix protein (COMP) and rheumatoid arthritis severity

Abstract: BackgroundSerum cartilage oligomeric matrix protein (COMP) is a non-collagen glycoprotein produced by the cartilage, synovium, tendon, and meniscus. Recent studies showed that COMP is a reliable factor for monitoring cartilage damage.ObjectiveTo determine the relationship between serum COMP concentration and the severity of rheumatoid arthritis (RA).MethodsThis cross-sectional study lasted from 2013 to 2015 at the Rheumatology Clinic of Ghaem Hospital, Mashhad, Iran. The study population consisted of eligible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 28 publications
(36 reference statements)
2
9
0
Order By: Relevance
“… 28 The s COMP level also has the potential to be used as a biological marker for differentiating between patients with rheumatoid arthritis (RA) and healthy individuals. 29 , 30 The relevance of COMP and bone development or disease has been identified by previous studies. 31 , 32 Based on our study results, it is necessary to further explore the potential of COMP in the diagnosis and treatment of KBD.…”
Section: Discussionmentioning
confidence: 90%
“… 28 The s COMP level also has the potential to be used as a biological marker for differentiating between patients with rheumatoid arthritis (RA) and healthy individuals. 29 , 30 The relevance of COMP and bone development or disease has been identified by previous studies. 31 , 32 Based on our study results, it is necessary to further explore the potential of COMP in the diagnosis and treatment of KBD.…”
Section: Discussionmentioning
confidence: 90%
“…Globally, most studies have shown that serum COMP level is higher in RA patients [13,14] . Consistent with these studies, our data also showed elevated COMP protein level in RA patients compared to normal controls.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with OA, these fragments are ~110 kDa in size, similar to the peptides generated by in vitro digestion of COMP with ADAMTS7 and 12 66 . Gene expression of both of these ADAMTS proteases is also elevated in the cartilage and synovium of patients with rheumatoid arthritis, where COMP levels are correlated positively with disease severity and negatively with cartilage thickness 18,69 …”
Section: Adamts Protease and Their Substrates In Musculoskeletal Devementioning
confidence: 95%
“…66 Gene expression of both of these ADAMTS proteases is also elevated in the cartilage and synovium of patients with rheumatoid arthritis, where COMP levels are correlated positively with disease severity and negatively with cartilage thickness. 18,69 The function of the COMP-degrading proteases in musculoskeletal development extends beyond their indications in arthritis. ADAMTS7 and 12 may regulate tendon development and prevent premature aging, coexpressed to preserve tendon cell identity.…”
Section: Comp-degrading Proteasesmentioning
confidence: 99%